Perancangan Aplikasi Mobile Android Dan Web "Host Kita" Untuk Ekosistem Promosi UMKM - Lazuardi, Maulana Fajar; Malabay (IKRA-ITH Informatika : Jurnal Komputer dan Informatika, 2025)
The Host Kita Android application is an innovative solution that allows SMEs (Small and MediumEnterprises) to access and utilize services from Live Streaming Hosts more easily. This applicationemerges in response to current trends; many SMEs aim to leverage the promotional potential oflive streaming on E-commerce platforms due to increased revenue following the implementationof live streaming business strategies. However, they often cannot afford to hire a full-time LiveStreaming Host, either due to budget constraints or small business scale. With the presence of theHost Kita application, SMEs can still utilize Live Streaming Host services to promote theirproducts. Thus, the role of the Host Kita application and Live Streaming Host services becomesmore effective and positively impactful. The design process of this application uses the RAD(Rapid Application Development) method, comprising four stages: Project Requirements,Prototype, Rapid Construction Feedback, and Implementation. This application is equipped withvarious features that will make it easier for MSMEs in their business processes. It is hoped thatthrough this application, SMEs can continue to grow significantly with the assistance of LiveStreaming Host services, and the SME business ecosystem can strengthen. The Host Kitaapplication has the potential to become a highly useful tool in supporting the promotion and marketing efforts of SME products on increasingly competitive E-commerce platforms, particularly on TikTok.